Tokyo Commute : Japanese Customs and Way of Life Viewed from the Odakyu Line - Lee, A. Robert, 1941- (Book collections on Project MUSE., 2011)
A unique take on modern life in Tokyo. A Japan of trains, every day to and fro, carriage scenes and theatre, vistas from the window, advertising posters. To be savoured through the Odakyu line. Pitched as creative text and line-graphics, Tokyo Commute offers on-track and off-track observations. Poetics of Japanese routine and etiquette.